Offspring Programming of central and peripheral nutrient-sensing pathways by the exposition to perinatal obesogenic environments - Gonçalves, Diana Sousa (2022)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia